Perbedaan Tingkat Kecemasan Ibu Bersalin di RSD Mangusada setelah Pemberian Teknik Distraksi Musik Klasik - Dewa Gede Adrian Harta Wiguna; I Gusti Ngurah Made Bayuningrat; Putu Indah Budi Apsari; I Made Pariartha; Ni Putu Indah Kusumadewi Riandra (Aesculapius Medical Journal, 2025)
The maternal mortality rate in Indonesia is one of the highest in the world. According to WHO, in 2017, 830 mothers in the world died due to complications that occurred during pregnancy and childbirth. One of the main factors causing maternal death according to WHO are prolonged labor. This research determine the differences in anxiety levels of mothers in the first stage of latent phase labor at the Mangusada Hospital after administering classical music distraction. Through this research, we can also determine the level of anxiety among mothers giving birth at the Mangusada Hospital using the PRAQ-R2 instrument which is valid and reliable. This research design uses quantitative research methods with an experimental and one group pretest posttest design. The sample in this study was all women giving birth in the first stage of the latent phase at the Mangusada Hospital from July to September with a total of 40 people. Univariate analysis showed that the majority of mothers were 25 years old, primiparous, with a gestational age of 38 weeks. Then the difference anxiety level measured using a non-parametric test, namely Wilcoxon Sign Rank Test. Wilcoxon showed a significant reduction in anxiety levels in mothers in the first stage of labor after being given treatment. This is proven by the value p < 0.001. Based on the results of the analysis, there were differences in the anxiety levels of mothers in the first stage of latent phase labor at the Mangusada Hospital after giving classical music distraction techniques.